(untitled) (Research, Society and Development, 2022)
The present ecological study aims to analyze the cases of Dengue in the state of Maranhão during the period from 2014 to 2021 through secondary data from the Information System of Notifiable Diseases. The information was taken from SINAN and DATASUS reports, in addition to recent publications on the subject under study. Quantitative data were presented through charts, figures and tables, with their appropriate analyses. Among the main results, it is observed that 53,831 cases of dengue were reported in the State of Maranhão during the period from 2014 to 2021, with 2016 being the year with the highest number of dengue cases. It should also be noted that the same occurred predominantly in women, in people aged between 20 and 59 years old, of a race considered brown and who attended elementary school. It is known that it is the duty of the health professional to correctly classify dengue, thus enabling effective treatment for patients. In addition, the WHO is encouraging the advancement of dengue vaccine research.